Incomplete revascularization: what the surgeon needs to know - Leviner, Dror B.; Torregrossa, Gianluca; Puskas, John D. (Annals of Cardiothoracic Surgery; Vol 7, No 4 (July 31, 2018): Coronary Revascularisation—Cardiology for the Surgeon, 2018)
For many years, the concept of “complete revascularization” (CR) was considered an absolute truth in coronary surgery with improved long-term survival and a lower rate of reintervention. This was derived from early publications which showed a survival benefit for patients undergoing coronary artery bypass grafting (CABG) who received CR. Many advances in the field of coronary revascularization have been made in the years that passed since those publications, including more frequent use of percutaneous coronary intervention (PCI) in patients with multivessel disease (MVD). This has led some to question the importance of CR and raise the option of “reasonable incomplete revascularization” (IR) for selected patients. The definition of CR is variable in the literature with the two most common definitions being an anatomical (revascularization of all coronary segments with stenosis and larger than a predefined size) and a functional definition (where revascularization is considered complete if all ischemic and viable territories are reperfused). No randomized control trials have been conducted to compare complete versus IR, and a significant proportion of data is based on post hoc analysis of data from randomized control trials and registries. Multiple studies have proven that CR is achieved more frequently with CABG then with PCI. A review of the available data from the past three to four decades shows a trend toward improved results with CR, regardless of the reperfusion strategy chosen. This should impact the heart team discussion when choosing a revascularization strategy and impact the surgical decision making while preforming CABG. IR can be part of a hybrid revascularization strategy or be reserved for rare cases where the cost of achieving CR much outweighs the benefit.